Evaluation of fusion splicing of hollow-core fibers to conventional single mode fiber - Józwicki, Mateusz; Grzesiak, Maciej; Mergo, Paweł (Photonics Letters of Poland, 2026)
The paper presents the fusion splicing of a hollow-core fiber with a conventional single-mode fiber with the aim of preserving the internal hollow structure of the hollow-core fiber while achieving optimal mechanical strength and low optical loss at the splice. Each splice made at different filament power was evaluated by measuring power loss resulting from the splice along with proof testing and visual inspection of the splice and end face of the HCF after splice failure. Obtained results show a trade-off between power loss and splice strength. Highest splice strength was achieved at 16.0 W filament power equal to 2.32±0.09 N with the loss of 0.167±0.011 dB, while lowest loss of 0.010±0.004 dB with splice strength of 0.22±0.04 N was achieved at 13.0 W filament power. Full Text: PDF References M. S. Habib, J. E. Antonio-Lopez, C. Markos, A. Schülzgen, R. Amezcua-Correa, "Single-mode, low loss hollow-core anti-resonant fiber designs", Opt. Express 27, 3824 (2019). CrossRef P. Jarowski, "A Review of Antiresonant Hollow-Core Fiber-Assisted Spectroscopy of Gases", Sensors 21, 5640 (2021). CrossRef J. Shi, et al., "All-fiber highly efficient delivery of 2 kW laser over 2.45 km hollow-core fiber", Nat Commun 16, 8965 (2025). CrossRef Y. Min et al. "Fusion Splicing of Silica Hollow Core Anti-Resonant Fibers With Polarization Maintaining Fibers", Journal of Lightwave Technology 39, 3251 (2021). CrossRef R. Thapa, K. Knabe, K. L. Corwin, and B. R. Washburn, "Arc fusion splicing of hollow-core photonic bandgap fibers for gas-filled fiber cells", Opt. Express 14, 9576 (2006). CrossRef C. Wang, et al., "Ultralow-loss fusion splicing between negative curvature hollow-core fibers and conventional SMFs with a reverse-tapering method", Opt. Express 29, 22470 (2021). CrossRef F. Poletti, "Nested antiresonant nodeless hollow core fiber", Opt. Express 22, 23807 (2014), CrossRef J. Shi, X. Ye, Y. Cui, W. Huang, H. Li, Z. Zhou, et al. "All-Fiber Gas Cavity Based on Anti-Resonant Hollow-Core Fibers Fabricated by Splicing with End Caps", Photonics 8, 371 (2021). CrossRef A. Cheng, C. Wang, J. Xu, P. Zhang, Y. Zheng, S. Dai, "Humidity Sensor Based on a Hollow Core Fiber Anti-Resonant Reflection Optical Waveguide", Photonic Sens 15, 250202 (2025). CrossRef Z. Zhang, R. Li, C. Wang, M. Zhou, Y. Liu, and Y. Pang, "Fusion splicing of hollow-core to standard single-mode fibers using a gradient-index bridge fiber", J. Opt. Technol. 90, 42 (2023). CrossRef A.D. Yablon, R.T. Bise, "Low-loss high-strength microstructured fiber fusion splices using GRIN fiber lenses", IEEE Photon. Techn. Lett. 17, 180120 (2005), CrossRef M.Murawski, L.R.Jaroszewicz, K.Stasiewicz, "A photonic crystal fiber splice with a standard single mode fiber", Phot. Lett. Poland 1, 115 (2009). CrossRef